The impact of 10-valent and 13-valent pneumococcal conjugate vaccines on hospitalization for pneumonia in children: A systematic review and meta-analysis. Issue 43 (13th October 2017) - Alicino, Cristiano; Paganino, Chiara; Orsi, Andrea; Astengo, Matteo; Trucchi, Cecilia; Icardi, Giancarlo; Ansaldi, Filippo
Highlights: Since 2010, PCV10 and PCV13 became available for use in children. This meta-analysis assessed the impact PCV10 and PCV13 in pneumonia hospitalization among children. Novel PCVs reduced hospitalization for pneumonia in children <24 months and 24–59 months. Reduction was more pronounced for radiologically confirmed pneumonia with respect to clinically confirmed pneumonia. None of the studies included in this meta-analysis had been designed to directly compare the impact of PCV10 and PCV13. Abstract: Background: This systematic review and meta-analysis aimed at summarizing available data on the impact of PCV10 and PCV13 in reducing the incidence of CAP hospitalizations in children aged <5 years. Methods: A systematic search of the literature was conducted. We included time-series analyses and before-after studies, reporting the incidence of hospitalization for pneumonia in the periods before and after the introduction of PCV10 or PCV13 into the immunization program. Pooled estimates of Incidence Rate Ratio (IRR) were calculated by using a random-effects meta-analytic model. Results were stratified according to age-groups (<24 months and 24–59 months) and case definitions of pneumonia (clinically and radiologically confirmed pneumonia). Results: A total of 1533 potentially relevant articles were identified. Of these, 12 articles were included in the analysis. In children aged <24 months, the meta-analysis showed a reduction of 17% (95%CI: 11–22%, p-value < 0.001) an of 31% (95%CI: 26–35%, p-value < 0.001) in the hospitalization rates respectively for clinically and radiologically confirmed pneumonia, respectively, after the introduction of the novel PCVs. In children aged 24–59 months, the meta-analysis showed a reduction of 9% (95%CI: 5–14%, p-value < 0.001) and of 24% (95%CI: 12–33%, p-value < 0.001) in the hospitalization rates for clinically and radiologically confirmed pneumonia, respectively, after the introduction of the novel PCVs. High heterogeneity was detected among studies evaluating the hospitalization rate for clinically and radiologically confirmed pneumonia. Conclusions: The results of this study revealed a significant impact of PCV10 and PCV13 in reducing the hospitalizations for pneumonia, particularly in children aged <24 months and for radiologically confirmed disease. Further appropriately designed studies, comparing the impact of PCV10 and PCV13, are needed in order to obtain solid data on which to establish future immunization strategies.